Avocado asks, "What am I?" - Abe, Momoko (Orchard Books, 2020)
Avocado is feeling just fine in the fruit and veg aisle at the supermarket - until a young customer asks a difficult question: "Is an avocado a fruit or a vegetable?" Avocado doesn't know the answer either - and the question won't seem to go away! A brilliantly funny book about identity and being confident in your own skin.